Global prevalence of digital addiction in general population: A systematic review and meta-analysis. (March 2022) - Meng, Shi-Qiu; Cheng, Jia-Lu; Li, Yang-Yang; Yang, Xiao-Qin; Zheng, Jun-Wei; Chang, Xiang-Wen; Shi, Yu; Chen, Yun; Lu, Lin; Sun, Yan; Bao, Yan-Ping; Shi, Jie
Abstract: The present meta-analytic review aimed to synthesize the global prevalence characteristics of digital addiction in the general population. We searched PubMed, Embase, Cochrane Library, and PsycINFO for studies reporting prevalence of various subtypes of digital addiction published before October 31, 2021. Studies were eligible if they were published in peer-reviewed journals, used a validated tool to assess digital addiction, and passed the qualify assessment. In total, 498 articles with 507 studies were included in systematic review, and the meta-analysis included 495 articles with 504 studies covering 2, 123, 762 individuals from 64 countries. Global pooled prevalence estimates were 26.99% (95% CI, 22.73–31.73) for smartphone addiction, 17.42% (95% CI, 12.42–23.89) for social media addiction, 14.22% (95% CI, 12.90–15.65) for Internet addiction, 8.23% (95% CI, 5.75–11.66) for cybersex addiction, and 6.04% (95% CI, 4.80–7.57) for game addiction. Higher prevalence of digital addiction was found in Eastern Mediterranean region and low/lower-middle income countries. Males had higher risk for Internet and game addiction. An increasing trend of digital addiction during the past two decades was found, which dramatically worsened during COVID-19 pandemic. This study provides the first and comprehensive estimation for the global prevalence of multiple subtypes of digital addiction, which varied between regions, economic levels, time periods of publication, genders, and assessment scales. PROSPERO ID: CRD42020171117. Highlights: 1/4 general population could be affected by at least one subtype of digital addiction. Prevalence differed among subtypes of digital addiction, with big geographical variation. Low/lower-middle income countries had higher burden of digital addiction. Males had higher prevalence of Internet addiction and game addiction than females. Increasing trend of digital addiction was worsened by COVID-19 pandemic.